Penulisan Awal Autobiografi Dalam Sejarah Persuratan Islam: Early Autobiographical Writing in The History of Islamic Literature - Shaary, Ahmad Marzuk; Abdul Hamid, Ahmad Faisal (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2021)
Autobiographical writing is a historical literary writing that reveals the author's views on himself, man and the environment around his life. This article reviews the development of autobiographical writing in Islamic history, also reviews five autobiographical writings written by several Islamic scholars and philosophers to describe the form and approach used by them. It can be concluded that, autobiographical writing in Islam is not a complete imitation of an external civilization encompassing concepts and forms. On the other hand, Islamic autobiography has its own characteristics and approaches apart from developing various forms of writing.